STUDI MORFOMETRI IKAN WADER GOA (Puntius microps Gunther, 1868) YANG UNIK DAN DILINDUNGI UNDANG-UNDANG - Haryono Haryono (The East Java Biological Society, 2006)
Wader goa (Puntius microps) is an endemic fish species and has unique habitat especially at cave in Java, also was protected by Indonesian Government therefore interesting to study. This fish related to Wader Cakul (Puntius binotatus) that wide distributed. The aims of study are to know the distinctive characters of both species by morphomethric and meristic methods. The results show that both species was different by morphometric and can not separated by meristic. The main characters are HW, SNL, ED, CPL and MXBL that joined of three functions showed 100% separated. Among P. binotatus, population from Java more related to Sumatra than Kalimantan.